Comparison of antibiotic susceptibility in viridans group streptococci in low and high antibiotic‐prescribing General Practices. (21st January 2015) - Goldsmith, C. E.; Hara, Y.; Sato, T.; Nakajima, T.; Nakanishi, S.; Mason, C.; Moore, J. E.; Matsuda, M.; Coulter, W. A.
Summary What is known and objective Antibiotic resistance has become a global public health issue. Most antibiotics are prescribed in the community, although there is less stewardship of such agents in the community compared to secondary and tertiary care. Few studies have attempted to examine the prescribing practices in General Practice and its impact on antibiotic resistance and, therefore, a study was performed in order to compare antibiotic susceptibilities of commensal viridans group streptococci (VGS) obtained from patient cohorts in General Practices (GP), who were high and low prescribers of oral antibiotics. Method Sixty‐five patients (<1 month–81 years; 77% female: 23% male) were enrolled onto the study, and viridans group streptococci (n = 5/patient) were collected from each patient's nasal passages and oropharynx region and tested for antibiotic susceptibility against (i) tetracyclines (doxycycline); (ii) macrolides (erythromycin); (iii) β‐lactams (penicillin G); and (iv) fluoroquinolones (ofloxacin & levofloxacin). Results and discussion There were no significant differences in MICs between high and low GP prescribers with doxycycline (P = 0·094), erythromycin (P = 0·122), ofloxacin (P = 0·193) and levofloxacin (P = 0·058). However, there was a significant difference between high and low GP practices with regard to penicillin G (P = 0·031). This finding is important as the β‐lactams are the most commonly prescribed oral antibiotic in the community. What is new and conclusion This study demonstrates that high prescribing practices may lead to an altered (higher) level of resistance to these agents in the commensal VGS population, which may be important as reservoirs of antibiotic resistance determinants in subsequent horizontal gene transfer events, particularly with newly colonizing pathogens, including pneumococci. Primary care physicians should be aware that increased prescribing of antibiotics may led to increased level of penicillin resistance.